The Influence of Democratic Leadership on Employee Performance With Organizational Commitment as an Intervening Variable in the Population and Civil Registry Office of Binjai City - Yani Utami Leo; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The role of employees in achieving organizational goals is undeniable, along with their behavior and performance which has a significant impact on the overall performance of the organization. Understanding the relationship between democratic leadership, employee performance, and organizational commitment, creates new challenges in optimizing organizational potential. The purpose of this study is to find out and analyze the influence of Democratic leadership on Employee Performance mediated by Organizational Commitment at the Population and Civil Registration Office of Binjai City. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 61 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that Democratic Leadership has a positive and significant effect on Employee Performance with a T-Statistical value of 0.2,182 > 1.96 and a P-Value of 0.033 < 0.05, as well as Democratic Leadership has a positive and significant effect on Organizational Commitment with a T-Statistical value of 44,165 > 1.96 and a P-Value of 0.000 < 0.05. However, Organizational Commitment has no effect on Employee Performance with a T-Statistic value of 1.956 < 1.96 and a P-Value of 0.055 > 0.05. Likewise, the organization's commitment was unable to intervene in the influence between Democratic Leadership on Employee Performance with a T-Statistical value of 1.943 < 1.96 and a P-Value of 0.057 > 0.05. These results provide insight into the existence of other mediating factors that can affect the relationship between leadership style and employee performance at the Binjai City Population and Civil Registration Office.